The differences in the effectiveness of football game between the best teams in XII European championship in 2008 - Buraczewski, T.; Cicirko, L (7th World Congress on Science and Football (WCSF), 2011, 2011)
The aim of the observation of a football game performed by the best teams and national teams is to notice its basic technical-tactical characteristics. The aim of the study was to compare the frequency and effectiveness of technical-tactical actions performed by winning and losing football teams in chosen matches of 2008 European Championship. The following research questions have been formulated: Are there any differences in the frequency of applied technical-tactical offensive actions between winning and losing teams? The effectiveness of which actions conditions the victory in the match? Methods The material for the research comprised the observation of the footballers of two teams (Austria - Switzerland) who participated in XII European Championship Finals in 2008. Detailed observations were made for the play of 166 footballers from 11 countries in 8 matches. The total time of observation reached 720 minutes. The following research method was applied- systematic, outside observation categorized by such standardized research tool as the observation sheets proposed by Szwarc (2002). Analyses were conducted for the following technical-tactical actions: shots at the goal, passes; 1x1 play in offensive actions, receiving and losing the ball. Results & Discussion Taking the analysis of the obtained results into account, it should be stated that the winning teams differed from the losing ones in the effectiveness of performed actions with the ball. The winning teams` actions were more effective. A significant statistical differentiation was stated with reference to the shots at the goal (<0,05), passes performed in difficult situations (<0,05) as well as receiving the ball (<0,05). As far as the effectiveness of other actions with the ball is concerned, the winning teams took the advantage, too, but no significant statistical differences were stated. The analysis of the research results of many researchers (Kuhn 2005, Buraczewski 2009) indicated that there are small dissimilarities in the frequency of applying some technical-tactical actions with the ball in the play of top class teams. These differences lie in the effectiveness of their performance in offensive as well as defensive actions. Conclusion Footballers of losing teams were second to winning teams in terms of the effectiveness of shots performance, passes and receiving the ball, i.e. in the actions which, according to many researchers determine the victory in the match.